A Multi-Omics Approach for Rapid Identification of Large Genomic Lesions at the Wheat Dense Spike (wds) Locus - Wang, Zhenyu; Tao, Shu; Liu, Shaoshuai; Jia, Meiling; Cui, Dada; Sun, Guoliang; Deng, Zhongyin; Wang, Fang; Kong, Xingchen; Fu, Mingxue; Che, Yuqing; Liao, Ruyi; et al. (Frontiers in Plant Science, 2022)
Optimal spike architecture provides a favorable structure for grain development and yield improvement. However, the number of genes cloned to underlie wheat spike architecture is extremely limited. Here, we obtained a wheat dense spike mutant (wds) induced by 60Co treatment of a common wheat landrace Huangfangzhu that exhibited significantly reduced spike and grain lengths. The shortened spike length was caused by longitudinal reduction in number and length of rachis cells. We adopted a multi-omics approach to identify the genomic locus underlying the wds mutant. We performed Exome Capture Sequencing (ECS) and identified two large deletion segments, named 6BL.1 at 334.8∼424.3 Mb and 6BL.2, 579.4∼717.8 Mb in the wds mutant. RNA-seq analysis confirmed that genes located in these regions lost their RNA expression. We then found that the 6BL.2 locus was overlapping with a known spike length QTL, qSL6B.2. Totally, 499 genes were located within the deleted region and two of them were found to be positively correlated with long spike accessions but not the ones with short spike. One of them, TraesCS6B01G334600, a well-matched homolog of the rice OsBUL1 gene that works in the Brassinosteroids (BR) pathway, was identified to be involved in cell size and number regulation. Further transcriptome analysis of young spikes showed that hormone-related genes were enriched among differentially expressed genes, supporting TraesCS6B01G334600 as a candidate gene. Our work provides a strategy to rapid locate genetic loci with large genomic lesions in wheat and useful resources for future wheat study.